NEW THERMOBARIC CONSTRAINTS ON THE EXHUMATION HISTORY OF THE LIGURIDE ACCRETIONARY WEDGE, SOUTHERN ITALY - Invernizzi, Chiara; Bigazzi, Giulio; Corrado, Sveva; Di Leo, Paola; Schiattarella, Marcello; Zattin, Massimiliano (Ofioliti, 2008)
New constraints on the thermobaric evolution of the Liguride complex of the Southern Apennines are provided by inorganic and organic thermal indicators. In detail, quantitative data on the thermobaric signature of the medium-to low-metamorphic Frido Unit and non-metamorphic North-Calabrian Unit have been derived using different methodologies such as clay mineralogy, fluid inclusion microthermometry, fission tracks analyses, and organic matter maturity. A good convergence among data from different, indipendent methods was obtained. The Frido Unit underwent temperatures in the range of anchizone (250- 300°C) according to data derived from both clay mineralogy and fluid inclusion microthermometry. Pressure estimates by white mica b0 parameter are typical of accretionary wedges and in the range of 6-8 kbar.In the non metamorphosed North Calabrian Unit, clay mineralogy, organic matter maturity and fluid inclusion microthermometry record thermal conditions from diagenesis (~ 130°C) to the late diagenesis - anchizone boundary (~ 200°C) for the Crete Nere Fm., and diagenetic conditions (temperatures around 100-110°C) for the Saraceno Fm. In a regional framework, these data help to better constraint the thermal evolution of the units belonging to the Liguride complex with respect to the timing of final exhumation at 5-6 My, as suggested by apatite fission tracks data.